Electrochemical Exfoliation of Pillared‐Layer Metal–Organic Framework to Boost the Oxygen Evolution Reaction. Issue 17 (13th March 2018) - Huang, Jin; Li, Yun; Huang, Rui‐Kang; He, Chun‐Ting; Gong, Li; Hu, Qiong; Wang, Lishi; Xu, Yan‐Tong; Tian, Xiao‐Yun; Liu, Si‐Yang; Ye, Zi‐Ming; Wang, Fuxin; et al.
Abstract: Two‐dimensional (2D) materials and ultrathin nanosheets are advantageous for elevating the catalysis performance and elucidating the catalysis mechanism of heterogeneous catalysts, but they are mostly restricted to inorganic or organic materials based on covalent bonds. We report an electrochemical/chemical exfoliation strategy for synthesizing metal–organic 2D materials based on coordination bonds. A catechol functionalized ligand is used as the redox active pillar to construct a pillared‐layer framework. When the 3D pillared‐layer MOF serves as an electrocatalyst for water oxidation (pH 13), the pillar ligands can be oxidized in situ and removed. The remaining ultrathin (2 nm) nanosheets of the metal–organic layers are an efficient catalyst with overpotentials as low as 211 mV at 10 mA cm −2 and a turnover frequency as high as 30 s −1 at an overpotential of 300 mV. Abstract : MOF slicing : A pillared‐layer metal–organic framework (MOF), in which the catechol functionalized pillars can be oxidized and removed in an electrochemical process, gives ultrathin nanosheets (2 nm). These are efficient electrocatalysts for water oxidation at pH 13 with a low overpotential and high turnover frequency (TOF).